AKIBAT HUKUM PERNIKAHAN SIRI - Awaliah, Awaliah; Nur Qalbi, Vivi; Isnawidiawinarti Achmad , Andi Nurul Isnawidiawinarti Achmad; Allang, Achmad (Maleo Law Journal, 2022)
God created humans in pairs of their own kind to continue their offspring through legal marriage. In practice, marriages are not carried out in accordance with applicable regulations and are recognized by the state. There are still many people who carry out unregistered marriages which have both legal, social and psychological consequences. The purpose of this paper is to determine the understanding and knowledge of the legitimacy and legal consequences of unregistered marriages in the Uswatum Khasanah study group about unregistered marriages. The results showed that before the counseling was carried out they had the same perception about unregistered marriage and registered marriage because the point was to avoid adultery, after counseling they knew and understood the weaknesses of unregistered marriage, especially regarding the position of women and their offspring. This means that people do not understand the status of unregistered marriages, so intensive counseling is needed regarding unregistered marriages to community groups, especially those who are vulnerable to conducting unregistered marriages